Students' mathematical representation ability in solving contextual problems on circle material - Distya Haerani Saputri; Nur Izzati; NurAsma Riani Siregar (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aimed to describe students' mathematical representation ability in solving contextual problems on circle material. The approach used is a qualitative approach with a descriptive research type. The research subjects came from class VIII B SMP Negeri 15 Tanjungpinang and were selected from as many as eight students. Data collection was done through test techniques and semi-structured interviews. The research findings show that students have different mathematical representation abilities. Students with very high mathematical representation ability categories can master three mathematical representation indicators (visual, mathematical equations or expressions, and written words or text). Students with high categories are only able to master two indicators (visual and mathematical equations or expressions), students with medium categories are only able to master one indicator (visual or mathematical expressions), and students with fewer categories are not able to master all three mathematical representation indicators. The tendency of students to master the indicators of mathematical equations or expressions well is due to being able to use mathematical connection skills well.